Quality Evaluation and Comparative Analysis on Recommendations of Guidelines for Degenerative Lumbar Spinal Stenosis - AN Yi, CHEN Hong, ZHOU Yanji, LIU Luping, CHEN Qianji, LEI Yuan, SUN Yanyan, WANG Xiyou, LIU Changxin, ZHANG Yang, YU Changhe (Zhongguo quanke yixue, 2023)
Background Degenerative lumbar spinal stenosis (DLSS) is a costly disease that mainly occurs during the old age, which seriously affects the normal life. There are many treatment options for DLSS. The development and clinical application of high-quality clinical practice guidelines are major ways to improve the diagnosis and treatment of DLSS. Objective To provide a reference for the development and reporting of clinical practice guidelines of DLSS, with guidelines of DLSS evaluated using AGREEⅡ and RIGHT, from the perspectives of methodology and quality. Methods Databases were searched for clinical practice guidelines, consensuses and specifications about DLSS, including CBM, CNKI, Wanfang Data, VIP, PubMed, Medlive, WHO, the National Institute for Health and Care Excellence, Guidelines International Network, National Guideline Clearinghouse and Scottish Intercollegiate Guideline Network from January 1, 2010 to January 1, 2022. The methodological quality and reporting quality of included studies were evaluated by two raters independently. And the recommendations in the studies were compared under the uniform grading criteria. Results Six studies were enrolled, including four guidelines and two consensuses. One guideline is based on TCM, and the other three are evidence-based guidelines. The evaluation results of AGREEⅡ showed that the ratio of the actual total score to the full score of the six included studies was 78.2%, 53.6%, 45.7%, 37.7%, 28.2% and 15.0%, from highest to the lowest. RIGHT evaluation showed that the ratio of the actual total score to the full score of the four guidelines was 72.9%, 72.9%, 62.9% and 34.3%, from highest to the lowest. A total of 46 therapeutic and 11 non-therapeutic recommendations were developed in the six studies. Conclusion The methodological quality and reporting specification of the present DLSS guidelines and consensuses require to be further improved. Further reference should be made to international standards such as AGREE Ⅱ and RIGHT in the process of guideline development and reporting. Surgical treatment is the preferred recommendation for patients with moderate or severe DLSS.